Muscle architectural and physiological responses to immobilisation: impact of age and obesity - Ali, Arfan M. (2020)
Clinical scenarios of recovery from illness or injury both require acute, mandatory periods of bed rest or immobilisation. However, this inevitably leads to; muscle loss, muscle weakness and a number of negative health problems which may be exacerbated in the elderly and in the obese. Both ageing and obesity are accompanied by reduced habitual physical activity levels and impaired muscle metabolic health which may pose an additive burden on musculoskeletal health in these patients. Therefore, understanding musculoskeletal deterioration associated with immobilisation is a major public health issue and embodies a vital area for scientific investigation.